Analaisis Permasalahan dan Pengembangan Usaha Dodol Pangi - Risal, Risma Yana; M. Rukka, Rusli; Rahmadanih, Rahmadanih; Busthanul, Nurbaya; Amrullah, A. (Hasanuddin University, 2024)
This study aims to analyze the problems and development of dodol pangi product marketing in small and medium enterprises in Soppeng Regency, South Sulawesi. Dodol pangi is a processed pangi fruit product that has high economic potential but is still limited to the local market. This study uses the agrosystem development planning analysis method (APPAS), which includes analysis of situations, problems, goals, and business development planning. The results of the study show that the main problems faced are low sales, which are caused by limited marketing areas, low packaging quality, and lack of promotion and understanding of digital marketing. In addition, product quality is also affected by the use of production equipment that is still manual. This study designs a series of actions to improve marketing, including improving the ability of human resources in digital marketing, redesigning packaging by including halal labels, composition, nutritional value, and expiration dates, as well as the procurement of more modern production equipment. The implementation of marketing strategies through social media, e-commerce, and exhibitions is expected to expand the market and increase product demand. Based on calculations, by implementing these actions, it is hoped that turnover and net income can increase significantly, reaching the sales target of 3000 packs per month and net income of around IDR 20,000,000. This research contributes to the development of agro-industrial marketing strategies based on superior local products at the small and medium enterprise levels.